2009
DOI: 10.4269/ajtmh.2009.80.523
|View full text |Cite
|
Sign up to set email alerts
|

Five-Year Surveillance of Molecular Markers of Plasmodium falciparum Antimalarial Drug Resistance in Korogwe District, Tanzania: Accumulation of the 581G Mutation in the P. falciparum Dihydropteroate Synthase Gene

Abstract: In January 2007, Tanzania replaced sulfadoxine-pyrimethamine (SP) with artemether-lumefantrine for treatment of uncomplicated malaria. This study examined the impact of widespread SP use on molecular markers of Plasmodium falciparum drug resistance in blood samples from persons living in two villages in Korogwe District, Tanzania, from 2003 through 2007. The prevalence of the P. falciparum dihydropteroate synthase (Pfdhps) gene 581G mutation increased from 12% in 2003 to 56% in 2007 (P < 0.001), resulting in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
54
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 25 publications
9
54
1
Order By: Relevance
“…Therefore, it could be opined that CQ sensitivity may be returning to northeast Nigeria years after the withdrawal of CQ due to widespread resistance [14]. This is in accordance with previous studies that have shown a decline in prevalence of Pfcrt 76T allele in parts of Africa such as Mali [43], Malawi [22], Kenya [44], Tanzania [45], Senegal [46], and now Nigeria. However, this calls for a larger study to re-assess CQ sensitivity in Nigeria.…”
Section: Discussionsupporting
confidence: 84%
“…Therefore, it could be opined that CQ sensitivity may be returning to northeast Nigeria years after the withdrawal of CQ due to widespread resistance [14]. This is in accordance with previous studies that have shown a decline in prevalence of Pfcrt 76T allele in parts of Africa such as Mali [43], Malawi [22], Kenya [44], Tanzania [45], Senegal [46], and now Nigeria. However, this calls for a larger study to re-assess CQ sensitivity in Nigeria.…”
Section: Discussionsupporting
confidence: 84%
“…15 Since this study, studies in Tanzania, 16 Kenya, 17 Senegal, 18 and Mozambique 19 have shown similar trends of reemergence of CQ sensitivity, and it is tempting to consider reintroduction of CQ in combination with another antimalarial drug in areas where CQ resistance has decreased and possibly reserved for malaria treatment of targeted populations, such as pregnant women, as has been suggested by others. 20 Another marker of antimalarial drug resistance is the P. falciparum multidrug resistance gene-1 (Pfmdr-1) implicated in resistance/tolerance to almost all antimalarial drugs including CQ, amodiaquine (AQ) and most importantly, the artemisinins.…”
Section: Introductionmentioning
confidence: 53%
“…32 The triple mutations, S108N, N51I, and C59R were evident in 100%, 93%, and 57% of isolates, respectively, in recent surveys in Angola 33 and in Tanzania, 100%, 100%, 100%, and 100% of isolates for 59R, 108N, 436S/437G, and 540E, respectively, in 2007 from a low transmission area. 34 Data from Uganda also showed within 99%, near 99%, and 57-94% of isolates respectively for the 108, 51, and 59 mutations. 35 Mockenhaupt and others 36 reported 72%, 56%, and 65% of isolates respectively for 108, 51, and 59 in Ghanaian isolates from samples collected in 2005 from Tamale in the northern region when the implementation of the new policy began.…”
Section: Discussionmentioning
confidence: 99%